Against strict headedness in syntax - Timm Lichte (Journal of Language Modelling, 2022)
Strict headedness is a common idealization in the structural analysis of linguistic entities, particularly in syntax. This contribution takes a critical look at its premises and applications by demonstrating the surprising sloppiness of both the defining concepts and the test procedures, and by showing how strict headedness is nevertheless implemented as an important axiom into virtually all mainstream grammar formalisms. Subsequently, I present a non-trivial head-agnostic analysis based on Tree Unification & Constraints (TUCO) in order to show that there actually is a choice and that strict headedness can be avoided in principle.